Measurement of compassion fatigue in animal health care professionals: a systematic review of available instruments and their content validity - Noe, May Thet Nu; Baysal, Yigit; Masserey, Anaïs; Hartnack, Sonja; Guseva Canu, Irina (Frontiers in Veterinary Science, 2024)
Compassion fatigue (CF) refers to emotional or physical exhaustion and emotional reactions resulting from prolonged exposure to traumatic events, commonly experienced by professionals in caregiving roles. CF is prevalent among healthcare professionals, including those in animal care. Several Patient-Reported Outcome Measures (PROMs) were developed to measure CF, but their psychometric validity was not reviewed systematically. This study aims to identify and review the content validity of CF PROMs used in animal health care professionals.Literature was searched in PubMed, PsycINFO, and EMBASE (1973-2023). We included studies conducted in animal health care professionals, using a PROM to measure CF, reporting at least one psychometric property of this PROM, and published as original research. For each identified PROM, additional literature search was conducted to identify PROM development and content validation studies. Three independent reviewers evaluated the content validity of each PROM using COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) methodology and summarized the quality of evidence using a modified GRADE approach. The protocol was registered in PROSPERO (CRD42023433982) and results reported following PRISMA guidelines. Initially, 1709 studies were identified. After a double screening, 17 eligible studies were included. CF was measured using six different PROMs or their modified versions. Only one PROM specifically targeted animal health care professionals: the ProQOL-5 Veterinary Medicine Version. This and three other original CF PROMs were reviewed. For all PROMs, the quality of content validity was rated as insufficient due to deficiencies in the concept and items elicitation, inadequate target population representation, and inadequate details on cognitive interview procedures. The overall evidence quality was rated as low due to a limited number of PROM validation studies, poor methodological and reporting quality, and indirect result. There is a scarcity of studies examining CF within the target population, and the quality of evidence for content validity of the reviewed PROMs for CF measurement is currently low. CF definition and construct description in PROM development studies suffer from vagueness and seem inadequately reflected by the content of the reviewed PROMs. Further research with a robust methodology seems necessary to address the identified flows.